Numerical simulation for helping the development of psychometric instruments - Matas-Terrón, Antonio (Comité organizador X Conbreso Hispano Luso de Gerontología, 2014)
In geriatric diagnostic, the use of tests and scales is normal and really useful. However, there are really difficulties to develop new diagnostic instruments supported with optimal psychometric conditions. Often, the small samples are a serious problem for developing them. The numerical simulation is a mathematical process that can help to elaborate new instruments and evaluate their psychometric properties in case of adaptation, when those problems are found. This paper shows an example about how to use numerical simulation to get tabulation tables to assess a tag population with the Spanish version of the Test Your Memory scale, starting with a limited and small sample of real data. Several conclusions are commented, first the utility of numerical simulation. Second, about the apparent lack of psychometric support for using the Test Your Memory scale Spanish version.
Keywords: Métodos de simulación; Diagnóstico; Numerical simulation; R; Test Your Memory Scale; Diagnostic instruments